Strategies and results in cohort monitoring: an introspective look for the industrial engineering career at UNMDP (AACINI - International Journal of Industrial Engineering, 2024)
In the university education system, the study of variables linked to the evolution of cohorts is essential to have relevant information for decision-making. Directing educational efforts and policies to guarantee the permanence of students at the university and optimizing graduation rates contributes to improving the academic quality of careers. The article presents the results of the cohort monitoring study carried out in the Industrial Engineering degree program at the UNMDP, between 2003 and 2022. Based on the available data, the corresponding retention, dropout and graduation indicators were selected. Based on the results obtained, action proposals are presented to update the Tutoring System, detect subjects or thematic nuclei in which dropout and slowdown phenomena are deepened, as well as implement activities that promote the reduction of the real duration of the career.
Keywords: industrial engineering; cohort follow-up; slowdown; duration of university career